2013
DOI: 10.1089/scd.2012.0226
|View full text |Cite
|
Sign up to set email alerts
|

ActivatedNF-κBin Bone Marrow Mesenchymal Stem Cells from Systemic Lupus Erythematosus Patients Inhibits Osteogenic Differentiation Through Downregulating Smad Signaling

Abstract: Osteoporosis in patients with systemic lupus erythematosus (SLE) is thought to be the result of accelerated osteoclastogenesis induced by pro-inflammatory cytokines such as tumor necrosis factor (TNF). However, the molecular mechanisms involved in the osteoblastogenesis in SLE patients are not fully understood. We investigated the bone morphogenetic protein-2 (BMP-2)-induced osteoblastic capacity of bone marrow-derived mesenchymal stem cells (BMMSCs) from SLE patients and the TNF signaling system in determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 60 publications
1
55
0
Order By: Relevance
“…The activated R-Smads bind to the common Smad (Co-Smad, Smad4) to form complex, and then translocates to the nucleus along with a number of transcription factors to regulate the expression of target genes (13). BMPs can also activate the non-canonical Smad pathways, such as PI3K/Akt, mitogenactivated protein kinase (MAPK) and nuclear factor κB (NF-κB) (36)(37)(38). In the present study, we found that Res can increase the level of BMP7 in HCT116 cells, which implied that the anticancer activity of Res may arise from upregulating the expression of BMP7.…”
Section: Discussionmentioning
confidence: 99%
“…The activated R-Smads bind to the common Smad (Co-Smad, Smad4) to form complex, and then translocates to the nucleus along with a number of transcription factors to regulate the expression of target genes (13). BMPs can also activate the non-canonical Smad pathways, such as PI3K/Akt, mitogenactivated protein kinase (MAPK) and nuclear factor κB (NF-κB) (36)(37)(38). In the present study, we found that Res can increase the level of BMP7 in HCT116 cells, which implied that the anticancer activity of Res may arise from upregulating the expression of BMP7.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that there were abnormalities in actin cytoskeleton, cell cycling regulation, BMP/TGF-β, and MAPK signaling pathways in BM-MSCs from SLE patients [177]. Tang et al found that activated NF-κB pathway in SLE derived BM-MSCs inhibits the BMP-2-induced osteoblastic differentiation through BMP/Smad signaling pathway, suggesting that the impaired osteoblastic differentiation may participate in the pathology of osteoporosis in SLE patients [178]. Another research also found that BM-MSCs from SLE patients exhibited senescent behavior and are involved in the pathogenesis of SLE.…”
Section: Mscs and Slementioning
confidence: 99%
“…In their study, the differentiation potential was evaluated only microscopically, which did not allow them to obtain quantitative data. In a study by Tang et al, 26 reduced differentiation into osteoblasts of MSCs isolated from patients suffering from systemic lupus was detected.…”
Section: Discussionmentioning
confidence: 96%